2021
DOI: 10.3390/cancers14010034
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of the Removed Vaginal Cuff and Its Correlation with L1CAM in Low-Risk Endometrial Adenocarcinoma

Abstract: Objective: The aim of our study was to investigate the role of the excised vaginal cuff length as a prognostic factor in terms of DFS and recurrence rate/site, in low-risk endometrial cancer (EC) patients. Moreover, we correlated the recurrence with the expression of L1CAM. Material and Methods: From March 2001 to November 2016, a retrospective data collection was conducted of women undergoing surgical treatment for low-risk EC according to ESMO-ESGO-ESTRO consensus guidelines. Patients were divided into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Estrogen receptor (ER) positivity, phosphatidylInositol 3-Kinase/protein-kinase B (PI3K/AKT) mutations, progesterone receptor (PR) positivity, and L1CAM positivity are molecular characteristics found in tumors with worse prognosis, respectively, in 78%, 65%, 61%, and 28% and less frequently mutation of FBXW7 and FGFR2 genes in 9% and 7% of cases. These subgroups with precise molecular subtyping are particularly useful in G3 ECs and all high-risk ECs [26][27][28]. Bosse et al, considering a multicenter cohort of 381 patients with grade 3 EC, showed that the molecular subgroup with the best five-years OS and PFS was POLE, with 89% and 96%, respectively.…”
Section: Molecular and Genomic Profilingmentioning
confidence: 99%
“…Estrogen receptor (ER) positivity, phosphatidylInositol 3-Kinase/protein-kinase B (PI3K/AKT) mutations, progesterone receptor (PR) positivity, and L1CAM positivity are molecular characteristics found in tumors with worse prognosis, respectively, in 78%, 65%, 61%, and 28% and less frequently mutation of FBXW7 and FGFR2 genes in 9% and 7% of cases. These subgroups with precise molecular subtyping are particularly useful in G3 ECs and all high-risk ECs [26][27][28]. Bosse et al, considering a multicenter cohort of 381 patients with grade 3 EC, showed that the molecular subgroup with the best five-years OS and PFS was POLE, with 89% and 96%, respectively.…”
Section: Molecular and Genomic Profilingmentioning
confidence: 99%
“…Molecular characteristics found in EC with worse prognosis are Estrogen receptor (ER) positivity, phosphatidylInositol 3-Kinase/protein-kinase B (PI3K/AKT) mutations, progesterone receptor (PR) positivity, L1CAM positivity. These results suggest that it would be useful to perform a more detailed molecular analysis especially in high-risk ECs, which represent a subclass with complex and heterogeneous characteristics, refining therapeutic management in clinical practice [ 21 , 23 , 24 , 25 , 26 ]. Furthermore, EC generally affects patients with a higher rate of comorbidity, elderly or obese, the assessment of the state of women’s frailty is fundamental to customize treatment strategies and reducing the morbidity rate therapy-related [ 27 , 28 , 29 ].…”
mentioning
confidence: 99%
“…The integration of molecular classification in EC Risk classes has offered the possibility to improve the risk stratification and management of EC to choose patients eligible for adjuvant therapy or to avoid unnecessary treatment in low-risk EC and may low-volume EC disease. The surgicalpathological staging is standard strategy to assess that EC patients need adjuvant therapy, although available data available suggest that molecular classification may play a more accurate prognostic role than histological analysis [51][52][53][54][55][56]. The available pieces of evidence about the topic are scarce and the existing studies are based on small cohorts.…”
Section: Resultsmentioning
confidence: 99%